ANALISIS PENERAPAN SIMRS DENGAN TAM TERHADAP EFISIENSI PELAYANAN PENDAFTARAN PASIEN DI RSIA MPH PURBALINGGA - Hikmah, Luviatun; Purbasari, Wika; Safitri, Riana; Anggraeni, Nila Ayu; Krismonika, Osi (Jurnal Teknologi Informasi, Ilmu Komputer dan Manajemen, 2025)
Patient registration services are a crucial component of hospital operations as they represent the initial point of service delivery. The implementation of the Hospital Management Information System (SIMRS) is expected to improve the efficiency of these services. This study aims to analyze the effect of SIMRS implementation on the efficiency of patient registration services at RSIA MPH Purbalingga using the Technology Acceptance Model (TAM) approach. The research used a quantitative method by distributing questionnaires to administrative staff and analyzing the data with RapidMiner and Microsoft Excel. T-test results show that the Actual System Usage (ASU1 and ASU3) variables have a significant or marginally significant effect on Behavioral Intention, while Perceived Ease of Use (PEOU1, PEOU2, and PEOU3) variables did not show a significant influence. The F-test results indicate that the regression model is not statistically significant (p-value > 0.05), suggesting that the independent variables do not collectively explain the variation in system usage intention. In conclusion, SIMRS has the potential to enhance the efficiency of patient registration services through user comfort and habitual use. However, perceived ease of use is not proven to be a dominant factor influencing system adoption in this context. These findings suggest that factors beyond usability, such as user attitude and routine interaction with the system, may play a more critical role in effective SIMRS implementation.